Enjoying Learning Writing through Facebook Group - Aziz, Zulfadli Abdul; Khatimah, Husnul (Lingua Cultura, 2019)
This research showed the English as a Foreign Language (EFL) students in Aceh who struggle in learning English writing as they had a lack of interest in it. This descriptive qualitative study aimed to find out in what ways Facebook Group facilitate the enjoyment of the students in learning this skill. Data were collected using interviews and analyzed through thematic analysis. Ten students from UIN Ar-Raniry were purposely chosen for the interviews that was done one by one at a time. The research findings show that there are four themes causing participants enjoyment of the learning writing in the group: (1) it provides unlimited timing; (2) it facilitates the participants’ freedom and creativity; (3) it provides the interactive feedback; and (4) it helps them in brainstorming the ideas. These four themes directly enhance the students’ situational interest in learning writing related to an environmental factor, but it results in the development of their individual interest. This research suggests that the teacher should combine the learning process in the classroom with the Facebook group media to fasten the enhancement of the learners’ writing skills. For the learners, it is suggested that they should utilize their social media such as Facebook group not only as their communication media but also for developing their learning in writing.